Examining the evolution of bully-victim behaviour in South African high school students - Namane, Kedibone Charlotte (Department of Information Systems, 2018)
Bully-victims have not been studied extensively in the South African context and studies regarding cyber bullying are not keeping up with this widespread of ICTs. There is a large scale of research that focuses on bullying and victimisation, but not much on bully-victims in general which makes it difficult to identify this group of individuals for better intervention measures. The term bully-victims refers to those individuals that are bullies but also experience bullying as well. An obstacle in the development of interventions suitable for this phenomenon is the inability of researchers, teachers as well as learners to differentiate between the different forms of bullying. Failure to understand the distinctions in the forms of bullying may result in a domino effect of not understanding individuals' behavioural differences as well as bullies' risk profiles. Therefore, it would be very important to try and get an understanding of this behaviour and the possible causes which will help in developing tools that can assist in preventing the cycle of mobile bullying, and mobile bully-victimisation as well as raise awareness on the issue. This study will therefore target the category of mobile bully-victims, this class has not been studied extensively but recent developments show that it has extreme consequences for young people. This study identified different factors that impact on bully-victim behaviour and the evolution thereof. Following literature review, the researcher developed a conceptual framework illustrating the evolution of mobile bully-victim behaviour. The framework proposed that there are relationships between previous traditional bullying experience and (1) the school environment, (2) self-control/self-esteem, (3) age/grade, (4) retaliation and (5) technology which result in the evolution of mobile bully-victim behaviour. The conceptual framework was tested using a questionnaire which was distributed to grade 8 and 9 learners in four schools in the Mpumalanga province where 817 responses were obtained. A Frequency distribution test was run on factors of mobile bullying that are significantly associated with factors of mobile victimisation and it was found that a total of 121 learners scored high on both these factors thus making them mobile bully-victims. It was also found through the execution of a Spearman rank order correlation that learners that currently use their mobile phones to bully others are those that were victims of previous traditional bullying. The results revealed, for example, that learners tend to threaten, spread rumours, share content online and create groups solely for the purpose of excluding others because they have been bullied in the past. Studies explain that this reaction is as a result of impulsivity, a characteristic of low self-esteem or lack of self-control, after experiencing bullying. Structural Equation modelling was run to analyse how bully-victim behaviour evolves and how the bully-victim pathways are formed. The results revealed that schools located in rural or less advantaged communities engage in bullying activities more than those in urban or suburban communities. It was also found that only 14% of learners were aware or knew of exiting anti-bullying policies in their schools and 40% indicated that they know of other mobile bullying reporting mechanisms, with most of these learners being from urban and suburban schools. Studies found that this may be due to the high social capital provided by well off communities which provide a safer environment. The findings also proved that learners are more involved in mobile bullying activities at a younger age, this contradicting previous studies which found that mobile bullying is more prevalent as children mature. Also, younger learners lack self-control/self-esteem due to previous traditional bullying experience whereas for older learners it is due to mobile bullying experience. This is despite the fact that studies show that self-control improves with age.